2004
DOI: 10.1021/la048221w
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Properties of Mixed Self-Assembled Monolayers on Gold Electrodes Containing Mercaptooctylhydroquinone and Alkylthiols

Abstract: Mixed self-assembled monolayers of 2-(mercaptooctyl)hydroquinone (QH2) and alkylthiols were formed on gold electrodes in EtOH and the redox process of the hydroquinone moiety of QH2 was characterized by cyclic voltammetry (CV) in 0.1 M H(2)SO(4). The monolayers were formed at a series of QH2:alkylthiol ratios and the QH2:alkylthiol ratio in solution was compared to the electrochemical response from QH2 in the obtained monolayer. Mixed monolayers of QH2 with hexylthiol, dodecylthiol, and octadecylthiol were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 44 publications
4
26
2
Order By: Relevance
“…Mixed SAMs of thiol-functionalized antraquinones and 1-alkanethiols showed the improved reversibility of redox process [23]. Studies of the mixed hydroquinone-terminated SAMs revealed the crucial influence of the chain length of diluent alkanethiol on the hydroquinone head-group electrochemical response [24]. We have composed mixed monolayers consisting of compound 2b and n-heptanethiol (HT) (Fig.…”
Section: Redox Properties Of Mixed Monolayersmentioning
confidence: 99%
“…Mixed SAMs of thiol-functionalized antraquinones and 1-alkanethiols showed the improved reversibility of redox process [23]. Studies of the mixed hydroquinone-terminated SAMs revealed the crucial influence of the chain length of diluent alkanethiol on the hydroquinone head-group electrochemical response [24]. We have composed mixed monolayers consisting of compound 2b and n-heptanethiol (HT) (Fig.…”
Section: Redox Properties Of Mixed Monolayersmentioning
confidence: 99%
“…SAMs from thiols have been extensively investigated since the 1980s of the preceding century [2][3][4][5] due to many diverse applications of such surfaces. For example, when a thiol monolayer is chemisorbed on a metallic electrode, the electrochemical characteristic of the metal is drastically changed and, depending on the properties of the organic moiety, the monolayer insulates the metal surface from different components of the solution [6,7]. The chemisorption of thiols on steel was investigated in the aspect of anti-corrosion protection [8].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in previous studies, steric factors from the microenvironment surrounding the reacting site play an important role in interfacial reactions 7, 13. Therefore, SPOCQ was studied for a series of mixed monolayers with variable alkyl:quinone ratios (from 0:1 to 3:1).…”
mentioning
confidence: 92%